NURSES’ KNOWLEDGE ON PHLEBITIS IN PATIENTS WITH PERIPHERAL INTRAVENOUS CATHETERS AND ASSOCIATED FACTORS AT TAM ANH GENERAL HOSPITAL HANOI IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe the current status of nurses’ knowledge regarding phlebitis in patients with peripheral intravenous catheters in 2025 and to analyze associated factors.Methods: A cross-sectional descriptive study was conducted among nurses working in clinical departments at Tam Anh General Hospital, Hanoi from May to December 2025. Data were collected using a structured, self-designed questionnaire developed based on literature review and guidelines. Nurses were considered to have adequate knowledge if their total score reached at least 70%.Results: Overall, 52.9% of nurses demonstrated adequate general knowledge of peripheral intravenous phlebitis. Male gender (OR = 2.07, p < 0.05), lack of supervision or audit during peripheral intravenous catheter insertion (OR = 2.80, p < 0.001), and lack of experience in caring for patients with phlebitis following catheterization (OR = 1.87, p < 0.001) were significantly associated with inadequate knowledge among nurses.Conclusions: The proportion of nurses with adequate knowledge of peripheral intravenous phlebitis was moderate (52.9%). Factors associated with nurses’ knowledge included gender, supervision, and clinical care experience.
Keywords: Phlebitis, peripheral intravenous catheter, knowledge, nurses.